1993
DOI: 10.1161/01.hyp.22.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Circadian blood pressure variation in transgenic hypertensive rats.

Abstract: Automatic, around-the-clock blood pressure measurements have increased our understanding of hypertension in humans. Patients with essential hypertension display patterns similar to those observed in nonnotensive subjects, whereas those with secondary hypertension frequently show abnormal circadian rhythms characterized by a failure to reduce blood pressure at night. We have modeled this situation in rats. Nonnotensive Wistar-Kyoto and Sprague-Dawley rats, spontaneously hypertensive rats, and rats made hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
83
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(92 citation statements)
references
References 11 publications
8
83
1
Order By: Relevance
“…Accordingly, a lower glomerular filtration rate and/or sodium reabsorption in mice compared with rats could contribute to lower Epo production and reduced Hct. In male rats raised at altitude, f H was around 500 beats min −1 , whereas normal sea level values of f H are around 250-300 beats min −1 during daytime and 350-400 beats min −1 during night-time (Lemmer et al, 1993). However, it is not possible from our data to elucidate whether the elevated f H effectively increases cardiac output or compensates for a reduced stroke volume.…”
Section: Discussionmentioning
confidence: 57%
“…Accordingly, a lower glomerular filtration rate and/or sodium reabsorption in mice compared with rats could contribute to lower Epo production and reduced Hct. In male rats raised at altitude, f H was around 500 beats min −1 , whereas normal sea level values of f H are around 250-300 beats min −1 during daytime and 350-400 beats min −1 during night-time (Lemmer et al, 1993). However, it is not possible from our data to elucidate whether the elevated f H effectively increases cardiac output or compensates for a reduced stroke volume.…”
Section: Discussionmentioning
confidence: 57%
“…Cosinor or spectral methods 11,12 are designed to identify the major frequency components of oscillatory behavior, and are therefore extremely powerful for studies in which this is the main feature of interest. Lemmer et al 11 used the former method to demonstrate differences between the circadian rhythms of Wistar-Kyoto (WKY), Sprague-Dawley, spontaneously hypertensive (SHR) and TGR[mRen-2]27 transgenic rats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the investigation of the diurnal rhythm, 49,54,55 radiotelemetry has been used to determine the effects of locomotor activity on blood pressure. A recent study in endothelial nitric oxide synthase (eNOS) knockout mice demonstrated that the size of the activity effect (23 mm Hg in controls, 33 mm Hg in eNOS knockouts) was far greater than the day-night difference in BP, or even the effect of knocking out the eNOS gene itself.…”
Section: Advantages and Applicationsmentioning
confidence: 99%